KERJASAMA INDONESIA-TIONGKOK DIBIDANG INFRASTRUKTUR PELABUHAN DALAM IMPLEMENTASI ONE BELT ONE ROAD (OBOR) DI INDONESIA PERIODE 2015-2017 - Anugrah Dien Pratama, - (2018)
The port is one of the important elements for a maritime country in improving its social and economic activities, Indonesia as a maritime country that is natural resources and strategically located is considered to be less maximizing its potential especially in port infrastructure due to many ports that are not internationally standardized in terms of facilities. Adequate or other supporting infrastructure. The Indonesian government has set a sea toll policy as the main focus to achieve national interests as the Poros Maritim Dunia (PMD) The government's efforts to improve the port by utilizing inventory opportunities in the One Belt One Road (OBOR) policy especially in Century Maritime Silk Road (CMSR) of Tiongkok. Indonesia-Tiongkok cooperates to help programs that are expected to improve port infrastructure, removing trade barriers. To oversee the trade route in the Indonesian sea and connect the two countries to the scheme CMSR scheme and to achieve common interests. But on the other hand the collaboration will only benefit Tiongkok to achieve its national interests through the modern silk belt of One Belt One Road